Transcriptional Synergy between Melanoma Antigen Gene Protein-A11 (MAGE-11) and p300 in Androgen Receptor Signaling - Askew, Emily B. (American Society for Biochemistry and Molecular Biology, 2010)
Androgen receptor (AR)-mediated gene regulation involves interactions with coregulatory proteins that include the melanoma antigen gene protein-A11 (MAGE-11). To understand the functional significance of sequence similarity between MAGE-11 and the adenovirus early protein E1A, we determined whether MAGE-11 contributes to AR transcriptional activity through an interaction with p300, a potent and ubiquitous transcriptional regulator. Here, we report that MAGE-11 interacts with the NH(2)-terminal region of p300 through the MAGE-11 MXXIF motif (185)MXXIF(189), with transcriptional activity depending on the MAGE-11 F-box and MAPK phosphorylation. The MAGE-11- and p300-dependent increase in AR transactivation required the NH(2)-terminal regions of AR and p300, p300 acetyltransferase activity, and the AR FXXLF motif (23)FQNLF(27) interaction with MAGE-11. MAGE-11 linked AR to p300 and the p160 coactivator, transcriptional intermediary protein 2 (TIF2). The p300 NH(2)-terminal FXXLF motif (33)FGSLF(37) was required for transcriptional activation by TIF2. Increased expression of p300 decreased the ubiquitinylation of MAGE-11 and transiently increased endogenous MAGE-11 levels. Autoacetylation of p300 and decreased acetylation of TIF2 were evident in the MAGE-11, p300, and TIF2 complex. The studies suggest that MAGE-11 links NH(2)-terminal domains of AR and p300 to promote transcriptional synergy through a cadre of FXXLF-related interacting motifs.